Julie Walters, Seriously Funny : The Unauthorised Biography - Ellis, Lucy; Sutherland, Bryony (London Virgin Books Ltd., 2003)
From her Oscar-nominated film debut alongside Michael Caine in "Educating Rita", to her appearances in "Billy Elliot" and the Harry Potter films, Julie Walters is one of Britain's finest actresses. This biography traces her life from a poor Birmingham upbringing to international acclaim.
Include Illustration, Chronology, Bibliography and Index.
The Unauthorised Biography.
Keywords: Great Britain -- Actresses -- Actors